2011
DOI: 10.1111/j.1365-3180.2011.00856.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of the newly invasive weed Flaveria bidentis (Asteraceae) reveals consequences of its rapid range expansion in northern China

Abstract: Ma JW, Geng SL, Wang SB, Zhang GL, Fu WD & Shu B (2011). Genetic diversity of the newly invasive weed Flaveria bidentis (Asteraceae) reveals consequences of its rapid range expansion in northern China. Weed Research51, 363–372. Summary The South American weed Flaveria bidentis has spread rapidly across northern China since its introduction to the Tianjin area in 2001. To explore its introduction dynamics and mechanism of rapid range expansion in northern China, we examined genetic diversity in 26 populations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 47 publications
0
20
1
1
Order By: Relevance
“…The values were much higher than in several other invasive species of Asteraceae in China Tang et al, 2009;Ma et al, 2011), and were even higher than in a previous study using inter-SSR (ISSR) markers for this species in southern China (Wang et al, 2008). Although SSR markers could reveal much more genetic variation than ISSRs, the results were unexpected for these roadside populations, which had short invasive histories (10-20 years).…”
Section: Genetic Diversity and Invasivenesscontrasting
confidence: 68%
See 4 more Smart Citations
“…The values were much higher than in several other invasive species of Asteraceae in China Tang et al, 2009;Ma et al, 2011), and were even higher than in a previous study using inter-SSR (ISSR) markers for this species in southern China (Wang et al, 2008). Although SSR markers could reveal much more genetic variation than ISSRs, the results were unexpected for these roadside populations, which had short invasive histories (10-20 years).…”
Section: Genetic Diversity and Invasivenesscontrasting
confidence: 68%
“…The AMOVA indicated that most of the genetic variation (91 %) resided within populations, rather than among populations (9 %) or among regions (highways, 0 %). The level of genetic differentiation among populations (F ST ¼ 0Á044, P < 0Á01) was much lower than the values reported for several other invasive species of Asteraceae in China Tang et al, 2009;Ma et al, 2011). Considering that the populations studied were located on the roadsides of four highways (from different directions) and were at least 40 km apart from each other, such a low level of genetic differentiation among populations was surprising.…”
Section: Genetic Diversity and Invasivenessmentioning
confidence: 58%
See 3 more Smart Citations